Vulvovaginal candidiasis in Iran: A systematic review and meta-analysis on the epidemiology, clinical manifestations, demographic characteristics, risk factors, etiologic agents and laboratory diagnosis. (May 2021) - Sasani, Elahe; Rafat, Zahra; Ashrafi, Keyhan; Salimi, Yahya; Zandi, Milad; Soltani, Saber; Hashemi, Farshid; Hashemi, Seyed Jamal
Abstract: Vulvovaginal candidiasis is a global issue of concern due to its association with economic costs, sexually transmitted infections, and ascending genital tract diseases. This infection affects 75% of women on at least one occasion over a lifetime. The present systematic review and meta-analysis is the first to determine the prevalence of vulvovaginal candidiasis in Iranian women. We searched national (SID, IranDoc, Iranmedex, and Magiran) and international (PubMed, Scopus, Google Scholar, and web of science) databases for studies published between May 2000 until May 2020 reporting the epidemiologic features of vulvovaginal candidiasis in Iranian women. Inclusion and exclusion criteria were defined to select eligible studies. Data were extracted and presented according to PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines. The results of the meta-analysis were visualized as a forest plot representing the prevalence estimates of each study. Heterogeneity was also analyzed using the I 2, and Chi 2 statistics. The literature search revealed 1929 studies, of which 39 studies met the eligibility criteria, consisting of 10536 women with vulvovaginal symptoms from 24 different cities covering all parts of Iran. The city with the highest number of studies was Tehran (5/39). The overall prevalence of vulvovaginal candidiasis among Iranian women was 47% (95% CI, 0/38–0/55%) and Candida albicans was the most prevalent etiologic agent. The use of oral contraceptive pills (OCPs) was the predominant risk factor for developing vulvovaginal candidiasis and vaginal cheese-like discharges were the predominant clinical manifestation in Iranian women suffering from vulvovaginal candidiasis. The 25-34-year-old age group has the highest prevalence. A high level of I 2 (I 2  = 98.7%, P  = 0.000) and Chi 2 (Chi 2  = 2993.57, P  < 0.001) was obtained among studies, which provides evidence of notable heterogeneity between studies. The present meta-analysis revealed a high prevalence of vulvovaginal candidiasis in Iranian women. Given that this infection is associated with the enhanced susceptibility to sexually transmitted diseases (HIV, chlamydia, genital herpes, genital warts, gonorrhea, hepatitis, syphilis, and trichomoniasis) and also is related to the increased probability of preterm birth, congenital cutaneous candidiasis, preterm labor, and infertility, taking preventive measures such as awareness of patients as well as monitoring and controlling of the syndrome are essential.